Long-Term Genomic Surveillance Unveils Key Drivers of Salmonella Contamination and Antimicrobial Resistance Dynamics in Surface Waters from Central Mexico - Enrique Jesús Delgado-Suárez; Santiago Zapata-Ramírez; Luz del Carmen Sierra-Gómez Pedroso; Francisco Alejandro Ruíz-López; Nayarit Emérita Ballesteros-Nova; Orbelín Soberanis-Ramos; María Salud Rubio-Lozano; Luisa María Sánchez-Zamorano; Yaselda Chavarin-Pineda; Rebecca Bell; Anna Brover; Maria Balkey; et al. (Water, Air, & Soil Pollution, 2026)

Emission of fine and ultrafine nanoparticle aerosols from composites functionalized with Multi-Wall Carbon Nano Tubes (MWCNTs) subjected to sliding wear: the influence of matrix material - Francisca Husanu; Juan Camilo Vélez Molina; Jesús Antonio Carlos Cornelio; Juan Felipe Santa Marín; Alejandro Toro; Marta Castellote; Roman Nevshupa (ENGINEERING Environment, 2026)
While multi-wall carbon nanotube (MWCNT)-reinforced nanocomposites offer improved wear resistance, the health implications of released nanoparticle aerosols are a concern. This research aimed to understand the influence of matrix material on the tribological properties, microstructure, and triboemission of MWCNT-functionalized polymer and cement composites. Key findings reveal that aerosol emission cannot be predicted solely based on porosity and mechanical properties. The observed variations in MWCNT effects across different matrix materials are attributed to the distinct dominant wear mechanisms in each.

Acoustic Indices Reveal Fundamental Differences in Daily Phenology of Tropical and Temperate Forest Soundscapes - Laura M. Berman; Santiago Perea; H. S. Sathya Chandra Sagar; Maia Persche; Grace Ingram; Tatiana Maeda; Natalie Yoh; Jorg Müller; Jens Schlüter; Nicolas Zapata; Ciara Wirth; Gonzalo Rivas‐Torres; et al. (Global Ecology and Biogeography, 2026)
Aim Forests support the majority of the planet's terrestrial biodiversity, and in recent years the characterisation of soundscapes has emerged as a powerful tool for understanding forest ecosystems, both in terms of ecology and for the purpose of conservation. But it is still poorly understood to what extent generalisations can be made about soundscapes in different parts of the world, and to what extent we should expect soundscapes to differ regionally. Here, we characterise the dominant acoustic features of forest soundscapes on a global scale and establish baseline expectations for how acoustic indices vary among biogeographic realms and biomes. Location Forests in Brunei, Ecuador, Gabon, Germany, Peru, Singapore, Sierra Leone and the USA, a dataset spanning two biomes and five out of six global biogeographic realms where forests occur. Time Period Two to five weeks of continuous audio data from each site collected between 2020 and 2024. Major Taxa Birds, amphibians, insects and mammals. Methods Stratifying data by time and frequency, we calculated four acoustic indices. Principal components analysis was used to compare the similarity of soundscapes across sites. Results Temperate and tropical forest soundscapes clustered separately in principal component analysis. Temperate forests had soundscapes which were uniformly loud during the day across all frequencies and were generally quiet at night. In contrast, all tropical locations had complex soundscapes during both day and night and had banding patterns suggestive of a high diversity of soniferous insects. These banding patterns were created by the unique soniferous community at each site, causing the ‘acoustic fingerprint’ of each site to be most similar to other sites in the same ecoregion and in the same biogeographic realm. The ‘acoustic fingerprints’ of temperate forest differentiated between ecoregions only when dawn was considered separately. Main Conclusions Our results stress the importance of using regional specific baseline data, as soundscapes are not necessarily comparable. Ecoacoustics is growing in popularity as an ecosystem monitoring tool, and understanding how forest soundscapes vary naturally across the globe can provide much needed context for studies that seek to understand factors that may disrupt or alter those soundscapes.

Phenolic content and profile of olive fruits: Impact of contrasting thermal regimes in non-Mediterranean growing environments - Pierluigi Pierantozzi; Mariela Torres; Cibeles Contreras; Vitale Stanzione; Martín Tivani; Luciana Gentili; Valerio Mastio; Peter Searles; Magdalena Brizuela; Fabricio Fernández; Alejandro Toro; Carlos Puertas; et al. (European Journal of Agronomy, 2025)

Changes derived by the silvopastoral management in Nothofagus antarctica forests of Tierra del Fuego compared to other productive environments - Guillermo Martínez Pastur; Yamina Micaela Rosas; Juan Manuel Cellini; Alejandro Huertas Herrera; Mónica D. R. Toro-Manríquez; María Vanessa Lencinas; Julieta Benítez; Sebastián Pechar; Pablo Luis Peri (Agroforestry Systems, 2024)

Early-life external exposome in children 2–5 years old in Colombia - Diana Marín; Xavier Basagaña; Ferney Amaya; Luis Miguel Aristizábal; Diego Alejandro Muñoz; Alan Domínguez; Francisco Molina; Carlos Daniel Ramos; Ricardo Morales-Betancourt; Roberto Hincapié; Laura Rodríguez-Villamizar; Yurley Rojas; et al. (Environmental Research, 2024)

Assessing the feasibility and sustainability of a surfactin production process: a techno-economic and environmental analysis - Johnny Alejandro Poveda-Giraldo; Juan Camilo Solarte-Toro; Chantal Treinen; Philipp Noll; Marius Henkel; Rudolf Hausmann; Carlos Ariel Cardona Alzate (Environmental Science and Pollution Research, 2024)
Biosurfactants have been profiled as a sustainable replacement for chemical-based surfactants since these bio-based molecules have higher biodegradability. Few research papers have focused on assessing biosurfactant production to elucidate potential bottlenecks. This research aims to assess the techno-economic and environmental performance of surfactin production in a potential scale of 65m 3 , considering different product yields and involving the European energy crisis of 2021–2022. The conceptual design, simulation, techno-economic, and environmental assessments were done by applying process engineering concepts and software tools such as Aspen Plus v.9.0 and SimaPro v.8.3.3. The results demonstrated the high economic potential of surfactin production since the higher values in the market offset the low fermentation yields, low recovery efficiency, and high capital investment. The sensitivity analysis of the economic assessment elucidated a minimum surfactin selling price between 29 and 31 USD/kg of surfactin, while a minimum processing scale for economic feasibility between 4 and 5 kg/h is needed to reach an equilibrium point. The environmental performance must be improved since the carbon footprint was 43 kg CO 2 eq/kg of surfactin. The downstream processing and energy demand are the main bottlenecks since these aspects contribute to 63 and 25% of the total emissions. The fermentation process and downstream process are key factors for future optimization and research.

Understory plant assemblage variations at different spatial scales: The case of Nothofagus forests in Tierra del Fuego - María Vanessa Lencinas; Alejandro Huertas Herrera; Juan Manuel Cellini; Marcelo D. Barrera; Magalí Pérez Flores; Mónica del Rosario Toro Manríquez; Julieta Benitez; Guillermo José Martínez Pastur (Journal for Nature Conservation, 2024)

Habitat type affects the diversity of dung beetle (Coleoptera: Scarabaeidae) assemblages in a neotropical mountainous region of Colombia - Renato Portela Salomão; Alejandro Lopera-Toro; Luz Astrid Pulido-Herrera; Jorge Armando Arias-Buriticá (International Journal of Tropical Insect Science, 2023)
Ecological communities of tropical regions respond to habitat configuration, being negatively affected by anthropogenic habitats. In the tropics, mountainous highland landscapes sustain ecological communities with contrasting responses to habitat transformation. This study assessed the effect of different habitats under different disturbance regimes on the dung beetle assemblage that inhabits a mountainous Andean landscape in Colombia. The habitat types surveyed were oak forest cores (low intervention), forest edges (medium intervention), and pastures (high intervention). A total of 3,810 dung beetles from ten species were collected. Dung beetle diversity was affected by habitat type, and forest cores and forest edges had higher diversity than pastures. Besides, each habitat type was characterized by a distinct dung beetle assemblage, with pastures showing the highest heterogeneity in the dung beetle assemblage. In conclusion, our study suggests that the dung beetles of a portion of Colombian Andean landscapes are sensitive to shifts of habitat quality. The higher dung beetle diversity in forested habitats indicates that pastures comprise limiting environments for their assemblages at this Andean region.

Combined effects of tree canopy composition, landscape location, and growing season on Nothofagus forest seeding patterns in Southern Patagonia - Mónica D.R. Toro-Manríquez; Alejandro Huertas Herrera; Rosina M. Soler; María V. Lencinas; Guillermo J. Martínez Pastur (Forest Ecology and Management, 2023)

Rehabilitation of Nothofagus pumilio forests in Chilean Patagonia: can fencing and planting season effectively protect against exotic European hare browsing? - Alejandro Huertas Herrera; Álvaro Promis; Mónica Toro-Manríquez; María Vanessa Lencinas; Guillermo Martínez Pastur; Matías Río (New Forests, 2022)

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Inferring population dynamic trends of Nothofagus pumilio and N. betuloides in coastal and mountain forests of Tierra del Fuego: contrasting from flowering to seedling survival through several reproductive cycles - Mónica D. R. Toro-Manríquez; Rosina Soler; Alejandro Huertas Herrera; María Vanessa Lencinas; Álvaro Promis; Ana Paula Blazina; Guillermo Martínez Pastur (Trees, 2022)

Acute meningoencephalitis associated with SARS-CoV-2 infection in Colombia - María A. Palacio-Toro; Johan S. Hernández-Botero; Daniela Duque-Montoya; Yuly Osorio; Alejandro Echeverry; Johanna J. Osorio-Maldonado; Marcela Orjuela-Rodríguez; Alfonso J. Rodríguez-Morales (Journal of NeuroVirology, 2021)

Conservation values of understory vascular plants in even- and uneven-aged Nothofagus antarctica forests - Guillermo J. Martínez Pastur; Yamina M. Rosas; Juan M. Cellini; Marcelo D. Barrera; Mónica DR Toro Manríquez; Alejandro Huertas Herrera; Santiago Favoretti Bondar; María V. Lencinas; Pablo L. Peri (Biodiversity and Conservation, 2020)

Early life stage bottlenecks of carnivorous molluscs under captivity: a challenge for their farming and contribution to seafood production - Iker Uriarte; Marcela Astorga; Juan Carlos Navarro; María Teresa Viana; Carlos Rosas; Carlos Molinet; Jorge Hernández; Jorge Navarro; Ignacio Moreno‐Villoslada; Rodolfo Amthauer; Gudrun Kausel; Jaime Figueroa; et al. (Reviews in Aquaculture, 2019)
This work brings together the view of different specialists in the areas of larviculture, physiology, ecology, nutrition and animal health, regarding how to deal with the aquaculture farming of species with complex life cycles in a multidisciplinary way, using as models the octopus and the muricid C. concholepas , with the aim of reducing the gap between the experimental and the industrial culture of species that are relevant for the diversification of aquaculture, particularly in Chile. Although these species are similar in their difficulty to reach the terminal planktonic phase prior to juvenile, they differ in the bottlenecks they have to overcome to reach it. Relevant aspects of study to achieve juvenile production from early life stages rearing, whether for repopulation or for ongrowing, are as follows: (i) Replacement or supplementation of live diets with inert diets to achieve significant survival values over the first stages of life. (ii) Physiological approaches to establish cultivation conditions evaluating the individual responses to several rearing conditions, specially the interaction between temperature, dissolved oxygen and acidity. Studies of urgent character due to the global warming scenario. (iii) Genomic studies associated with the effect of ontogenetic development, environment, health and nutrition on gene expression to understand, in an integrated way, the key processes for the development and growth of immature stages. (iv) Studies on the control of reproduction, the quality control of the ova, the genetic structure of reproductive populations and the characterization of diseases are also necessary to achieve efficient hatchery technologies.

Changes in the expression of genes involved in the ovarian function of rats caused by daily exposure to 3-methylcholanthrene and their prevention by α-naphthoflavone - Eric Alejandro Rhon-Calderón; Carlos Alejandro Toro; Alejandro Lomniczi; Rocío Alejandra Galarza; Alicia Graciela Faletti (Archives of Toxicology, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)